Membaca Mitos Perempuan Dalam Buku Surat-Surat Dari Mollo, Suatu Analisis Semiotika - Ratnasari, Sandra (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Letters from Mollo is a collection of stories and recipes by 12 authors. This book brings together literary, ecological, gastronomic, and architectural narratives from a place in the Mollo Mountains in South Central Timor. This book is an important literary work created to perpetuate regional wisdom in which women are the mainstay of life. This book focuses on the important presence of women in the daily life of the people of the Mollo Mountains. They showed pride in the role of women in protecting the Earth. Dissecting the book Letters from Mollo will make us understand more and more the role of Mollo women in saving the world. The work of the villagers who prioritize local wisdom will be studied using Roland Barthes’ semiotic theory so that messages through text and illustrations in the book will convey their meaning to readers. Understanding the book by means of this qualitative test will provide information on how great the Mollo women are. This book will open the eyes of the world to how important it is for humans to communicate with nature.